Dynamics of EU food safety certification: A survival analysis of firm decisions - Ragasa, Catherine; Thornsbury, Suzanne; Joshi, Satish (Springer, 2017)
The article empirically examines the timing of initial decisions to adopt food safetysystems and subsequent decisions to maintain the certification. Survival models areused to evaluate firm-level decisions among seafood processors in the Philippines.Whereas initial certification decisions were influenced mainly by easily obtain able apriori indicators such as output price, scale of production, and association membership,decisions to continue certification were influenced by a larger number of less-visiblefactors including price differentials across markets and cost structures. Managerialhubris may have played a role in initial certification decisions, but decertificationdecisions were more informed by realized cost–benefit comparisons. Results highlighttendencies to initially overestimate of benefits and underestimate costs of food safetycertifications, resulting in unrealistically optimistic projections and may lead to adversefirm performance.